EFISIENSI USAHA BUDIDAYA UDANG VANNAME - Jusmiaty Jusmiaty; Muhammad Akib Tuwo; Bahari Bahari (Jurnal Sosio Agribisnis, 2017)
This study aimed to analyze the effects of production factors on production volume; determine and analyze the technical, economic, and allocative level of efficiency of vanname shrimp farming.  The study was conducted at Sani-Sani village in Samaturu sub regency, Kolaka regency, involving 46 purposively-selected samples of shrimp farmers. Analysis was performed using the Frontier version 41.c program by applying the stochastic frontier approach to production function and cost function. Results of the study were: volume of production were affected by: farming area, urea fertilizer, shrimp feedings, shrimp seedlings, and labors. Production cost was affected by price of: volume production, urea fertilizer, SP36 fertilizer, lime, shrimp seedlings, and labors. The average technical efficiency, allocative efficiency and economic efficiency shrimp farming vanname in the classification efficiency was low because the value below 90 percent efficiency ranged between 80.99 to 88.64 percent of the use of factors of production is not efficient , which means they need additional factor production. Keywords: vanname shrimp; allocative; economic; technical efficiency; stochastic frontier